Interventional treatments for prolapsing haemorrhoids: network meta-analysis. Issue 5 (11th October 2021) - Jin, J Z; Bhat, S; Lee, K -T; Xia, W; Hill, A G
Abstract: Background: Multiple treatments for early–moderate grade symptomatic haemorrhoids currently exist, each associated with their respective efficacy, complications, and risks. The aim of this study was to compare the relative clinical outcomes and effectiveness of interventional treatments for grade II–III haemorrhoids. Methods: A systematic review was conducted according to PRISMA criteria for all the RCTs published between 1980 and 2020; manuscripts were identified using the MEDLINE, Embase, and CENTRAL databases. Inclusion criteria were RCTs comparing procedural interventions for grade II–III haemorrhoids. Primary outcomes of interest were: symptom recurrence at a minimum follow-up of 6 weeks, postprocedural pain measured on a visual analogue scale (VAS) on day 1, and postprocedural complications (bleeding, urinary retention, and bowel incontinence). After bias assessment and heterogeneity analysis, a Bayesian network meta-analysis was performed. Results: Seventy-nine RCTs were identified, including 9232 patients. Fourteen different treatments were analysed in the network meta-analysis. Overall, there were 59 RCTs (73 per cent) judged as being at high risk of bias, and the greatest risk was in the domain measurement of outcome. Variable amounts of heterogeneity were detected in direct treatment comparisons, in particular for symptom recurrence and postprocedural pain. Recurrence of haemorrhoidal symptoms was reported by 54 studies, involving 7026 patients and 14 treatments. Closed haemorrhoidectomy had the lowest recurrence risk, followed by open haemorrhoidectomy, suture ligation with mucopexy, stapled haemorrhoidopexy, and Doppler-guided haemorrhoid artery ligation (DG-HAL) with mucopexy. Pain was reported in 34 studies involving 3812 patients and 11 treatments. Direct current electrotherapy, DG-HAL with mucopexy, and infrared coagulation yielded the lowest pain scores. Postprocedural bleeding was recorded in 46 studies involving 5696 patients and 14 treatments. Open haemorrhoidectomy had the greatest risk of postprocedural bleeding, followed by stapled haemorrhoidopexy and closed haemorrhoidectomy. Urinary retention was reported in 30 studies comparing 10 treatments involving 3116 participants. Open haemorrhoidectomy and stapled haemorrhoidopexy had significantly higher odds of urinary retention than rubber band ligation and DG-HAL with mucopexy. Nine studies reported bowel incontinence comparing five treatments involving 1269 participants. Open haemorrhoidectomy and stapled haemorrhoidopexy had the highest probability of bowel incontinence. Conclusion: Open and closed haemorrhoidectomy, and stapled haemorrhoidopexy were associated with worse pain, and more postprocedural bleeding, urinary retention, and bowel incontinence, but had the lowest rates of symptom recurrence. The risks and benefits of each treatment should be discussed with patients before a decision is made. Abstract : This article reports a systematic review and network meta-analysis of RCTs comparing interventional treatments for grade II–III haemorrhoids, and provides a comparison and ranking of treatments according to their efficacy and complication profile. The results may inform decision-making regarding the most suitable treatment modality for haemorrhoids.